High‐Speed NIR‐Driven Untethered 3D‐Printed Hydrogel Microrobots in High‐Viscosity Liquids - Yin Chen; Mingliang Li; Qianqian Tang; Yifan Cheng; Anqi Miao; Liang Cheng; Shilu Zhu; Tingting Luo; Guangli Liu; Lijiu Zhang; Fuzhou Niu; Liang Zhao; et al. (Advanced Intelligent Systems, 2023)
Untethered synthetic microrobots have significant potential to revolutionize biomedical interventions therapy in the future. However, the relatively slow speed of microrobots and viscosity biofluid environments are some of barriers standing in the way of microrobots’ biomedical applications. Herein, inspired by high‐speed biological escape propulsion, NIR‐driven microrobots with a high‐speed, unidirectional propulsion in the high‐viscosity liquid are proposed. The bubble's growth and ejection cause the proposed 3D‐printed microrobot to propel forward. The 3D‐printed claw‐like microrobot achieves motion average speed of 1.4 mm s−1 (three‐body length (bl) s−1) when driven by NIR light in a pure glycerol viscous (945 mPa s, 25 °C) environment, which has a viscosity that is more than 200 times the viscosity of blood and of 54 mm s−1 (120 bl s−1) when driven by NIR light in deionized (DI) water. This work provides more ideas for the design and propulsion of light‐driven microrobots in a high‐viscosity vivo environment, which may broaden the applications of microrobots in the biomedical field, such as propulsion and navigation in confined and hard‐to‐reach body location areas.